Safari in South Africa - Lumry, Amanda; Hurwitz, Laura; McIntyre, Sarah (New York : Scholastic, 2008)
Riley joins his cousin Alice, Aunt Martha, and Uncle Max on an African safari, where they track and count baby wild animals, leading to close encounters with all kinds of animals.
School Library Journal
3.4
K-3
K-3
Keywords: Animals -- Infancy -- Juvenile fiction; Explorers -- Juvenile fiction; Safaris -- Juvenile fiction; Animals -- Infancy -- Fiction; Explorers -- Fiction; Safaris -- Fiction; Animal babies -- Fiction; Explorers -- Fiction; Safaris -- Fiction; South Africa -- Juvenile fiction; South Africa -- Fiction; South Africa -- Fiction